Quoting and trading in WAMZ currencies: Challenges and way forward - Eunice Ngozi Egbuna; Emmanuel Ating Onwioduokit; Marshall D. Umo; Kemoh Mansaray; Adedapo Adenekan (West African Monetary Institute (WAMI), 2012)
In the past few years, concerted efforts have been made by policy makers towards achieving full implementation of the quoting and trading in the West African Monetary Zone (WAMZ) national currencies as a precursor to full currency convertibility. Quoting and trading in WAMZ national currencies implies that these currencies are freely convertible and can be used to finance goods and services produced and traded in the Zone. Since the WAMZ convergence Council endorsed that commercial banks and other private financial institutions operating within the zone should pilot the quoting and trading in WAMZ currencies, not much has been achieved. The framework for currency convertibility would facilitate the eventual issuance of the single currency (ECO) by the common central bank (WACB). Thus, the full implementation of the quoting and trading in the WAMZ currencies is a precursor to meeting the basic requirements for currency convertibility, including strong commitment to sound macroeconomic management, exchange rate stability and adequate stock of international reserves. In the WAMZ, convertibility of member countries' currencies refers to the ease with which a Member State's currency can be converted into other local currencies within the Zone, to engender intra-regional trade. It is, therefore, crucial because it will eliminate the use of third party currencies (US dollars, euro, pounds, etc) from the trade links between and among the countries. The European experience has shown that the attainment of convertibility for groups of currencies requires coordinated and concerted efforts. In this regard, WAMZ member countries would be required to pursue policies aimed at achieving at the minimum, current account convertibility. This paper reappraises the issues concerning quoting and trading in the WAMZ currencies, highlights the challenges and proposes a new framework for jumpstarting the programme to facilitate currency convertibility within the Zone.
Keywords: 330; Quoting and Trading; WAMZ Currencies